Embryo sexing methods in bovine and its application in animal breed - Shelema Kelbessa Bora (Journal of Animal Reproduction and Biotechnology, 2022)
The ability to determine the sex of bovine embryos before the transfer is advantageous in livestock management, especially in dairy production, where female calves are preferred in milk industry. The milk production of female and male cattle benefits both the dairy and beef industries. Pre-implantation sexing of embryos also helps with embryo transfer success. There are two approaches for sexing bovine embryos in farm animals: invasive and non-invasive. A non-invasive method of embryo sexing retains the embryo’s autonomy and, as a result, is less likely to impair the embryo’s ability to move and implant successfully. There are lists of non-invasive embryo sexing such as; Detection of H-Y antigens, X-linked enzymes, and sexing based on embryo cleavage and development. Since it protects the embryo’s autonomy, the non-invasive procedure is considered to be the safest. Invasive methods affect an embryo’s integrity and are likely to damage the embryo’s chances of successful transformation. There are different types of invasive methods such as polymerase chain reaction, detection of male chromatin Y chromosomespecific DNA probes, Loop-mediated isothermal amplification (LAMP), cytological karyotyping, and immunofluorescence (FISH). The PCR approach is highly sensitive, precise, and effective as compared to invasive methods of farm animal embryonic sexing. Invasive procedures, such as cytological karyotyping, have high accuracy but are impractical in the field due to embryonic effectiveness concerns. This technology can be applicable especially in the dairy and beef industry by producing female and male animals respectively. Enhancing selection accuracy and decreasing the multiple ovulation embryo transfer costs.